PENGELOLAAN KEBERSIHAN DAN KESEHATAN LINGKUNGAN DI DESA SEMUT KECAMATAN WONOKERTO KABUPATEN PEKALONGAN - Mahirun Mahirun; Andi Kushermanto (LPPM Universitas Pekalongan, 2021)
The living environment is a unitary space with all objects, forces, conditions, and living things, including humans and their behavior that affect the continuity of life and the welfare of humans and other living creatures. Environmental awareness is an effort to grow and develop awareness of the environment which does not only include garbage, pollution, greening animal protection, but furthermore how people have a love for land and water to achieve justice, prosperity and environmental sustainability. This community service regarding the management of environmental hygiene and health is carried out in Semut Village, Wonokerto District, Pekalongan Regency with the target population of the village community. The purpose of this activity is to build a culture of environmental awareness and increase community participation in environmental hygiene and health. The results of the activity can run smoothly, as evidenced by the role of participants who follow from elements of the community, and more importantly the growing public awareness of the importance of protecting the environment which includes cleanliness and environmental awareness, and increasing public understanding and awareness about environmental hygiene and health. Assistance activities to the community by involving all related components from the village, sub-district, and related offices in Pekalongan Regency can be carried out to maintain the continuity of these activities.Keywords: Village, environment, environmental awareness, cleanliness, health